Anticancer activity of Nelumbo nucifera stamen extract in human colon cancer HCT-116 cells in vitro - Zhao, Xin (Oncol Lett, 2017)
The aim of the present study was to investigate the anticancer activities of Nelumbo nucifera (Ba lotus) stamen ethanol crude extract (BLSEE) in human colon carcinoma HCT-116 cells. MTT assay, flow cytometry analysis and reverse transcription-polymerase chain reaction assay were employed to investigate the anticancer mechanisms of BLSEE (100, 200 and 400 µg/ml) in HCT-116 cells. BLSEE reduced HCT-116 cell proliferation in a dose-dependent manner. BLSEE treatment also significantly increased the sub-G1 population in HCT-116 cells (P=0.0020 at 400 µg/ml), as shown by flow cytometry assay. Following treatment with BLSEE, the mRNA levels of the apoptosis-associated factors Fas, Fas ligand, tumor necrosis factor-related apoptosis-inducing ligand, death receptor 4 (DR4), death receptor 5 (DR5), caspases 3, 8 and 9, and B-cell lymphoma-2 (Bcl-2) associated X protein were increased, and the expression of anti-apoptotic Bcl-2 and Bcl-extra large was decreased in HCT-116 cells. The mRNA levels of matrix metalloproteinase (MMP)-2, MMP-9, TIMP metallopeptidase inhibitor 1 and TIMP metallopeptidase inhibitor 2 were also regulated by BLSEE treatment. In addition, BLSEE was able to modulate the expression of inflammation-associated nuclear factor-κB, inhibitory κBα, inducible nitric oxide synthase and cyclooxygenase 2 in HCT-116 cells. The present study clearly indicated the cytotoxicity of BLSEE in HCT-116 cells through induced cellular apoptosis. These results also suggested the BLSEE may be a powerful agent against colon cancer cells.